Anaemia and associated factors among standard 6 rural schools in Kuala Terengganu District Dicember 1994, 1995 - Rohayaty Muda,; Fatimah Arshad, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was done in December 1994 to determine the prevalence rate of anemia and the associated factors among standard six students in the district of Kuala Terengganu. Three schools was randomly selected from 65 schools in Kuala Terengganu which involved a sample of284 students. Data was obtained using a self-administered questionnaire, anthropometry measurement, 24-hour dietary recall, academic assessment and mental activities. The health knowledge of mothers of the students were also assessed using a self-administered questionnaire. The prevalence rate of anemia (Hb < 12 gm.%) was 12.7%. It is higher among female students. The other variables including nutrition intake, antropometry status, family size, sanitation and health knowledge of mothers did not show any significant difference between anemic and non anemic students. These could be due to the fact that the population is homogenous. There is a situation indicating lower school performance based on examination result of three subjects (English, mathematics and Human Science). However this study does not shows any significant difference. This could be due to other confounding factors such as severity of anemia, homogenesity of sample and others not studied. The mental performance of the student is measured by the duration to complete a set of activities involving puzzle, quiz and others was done. The linear regression analysis showed that for every I gm % decrease in level of hemoglobin of the children, there is an increase of 18 second in time to complete the mental activities. (p < 0.05, r = 0.19 and r = 3.8 %). These infer that anemia as indicated by the hemoglobin levels cause a decrease in attention spans of children conducting a set of mental activities. Since anemia is still prevalence among the school children in Kuala Terengganu screening of cases and follows up to over come the problem is importance to ensure that the children are alert at school.